Early childhood education and care in Ireland and Northern Ireland - Sarah Curristan; Frances McGinnity; Helen Russell; Emer Smyth (The Economic and Social Research Institute (ESRI), 2023)
Early childhood is a key life stage and early childhood experiences are crucial not only for children's well-being, but for their subsequent development. There is increasing evidence that social inequalities in outcomes emerge even before children start school, and a large body of international research highlights that investing in high-quality early childhood education and care (ECEC) can benefit children's cognitive and non-cognitive development. Affordable childcare has an important role in facilitating parental employment, which in turn can reduce child poverty. There has been increasing recognition of the importance of ECEC in both Ireland and Northern Ireland, with considerable recent energy and investment in early years policy in Ireland, and a renewed impetus in policy development in Northern Ireland given by the recent Fair Start report, which emphasised the importance of early years for tackling educational inequality (Expert Panel on Educational Underachievement in Northern Ireland, 2021). This report draws on survey and administrative data, as well as in-depth interviews with key stakeholders, to document the nature of early years provision in Northern Ireland and Ireland. It explores the use of different forms of early care and education in both jurisdictions, and how this varies for different groups of families. It also compares young children's cognitive and social outcomes, using survey data, and discusses the challenges related to early years provision.
Keywords: 330; Frühkindliche Bildung; Kinderbetreuung; Familienpolitik; Kognition; Soziale Kompetenz; Kinder; Nordirland; Irland